Audit committee and firm performance: a study on listed food, beverage and tobacco companies in Sri Lanka - Lingesiya, K.; Jeyan Suganya, D.F. (University of Jaffna, 2023)
The audit committee is one of the key elements in the corporate governance structure and helps to control and monitor management in the organization. The major aim of the study is to examine the impact of audit committee on the firm performance of listed food, beverage, and tobacco companies in Sri Lanka. Different characteristics of the audit committee such as audit committee size, audit committee meetings, audit committee independence and audit committee financial experts were used as independent variables while Tobin's Q and return on assets were considered as dependent variables. Further, firm size and financial leverage were used as control variables. Data was collected from a sample of 35 food, beverage, and tobacco companies listed in the Colombo Stock Exchange for six years from 2015 to 2020. Unit root analysis was employed for testing the stationery of the data and hypothesis was examined by using pooled regression analysis. The result of the study discovered that there is a significant positive impact of audit committee meetings and audit committee financial experts on Tobin's Q. Moreover, audit committee size has a significant positive impact on return on assets while audit committee independence has a significant negative impact on return on assets. The rest of the variables do not have any significant impact on the dependent variables. As per the result, listed food, beverage, and tobacco companies should increase the number of audit committee meetings and members of the audit committee particularly members who are experts in financial matters for uplifting performance of the firm by introducing new monitoring mechanism for reducing errors and frauds progressively.
Keywords: Audit committee; Audit committee independence; Audit committee experts; Audit committee meetings; Firm performance